Seni Video sebagai Medium kritikan sosial - Valerie, Anak Michael (Universiti Malaysia Sarawak (UNIMAS), 2007)
This research is to study video as a medium of expressing criticism toward social issue now a day. Apart from that, the researcher wants to observed audience's reaction through their interpretation and reflection on the issues which being highlighted in the video